Regenerating Regional Culture A Study of the International Book Town Movement - Frank, Jane (Sociology of the Arts ,, 2018)
This book explores the significance of the international book town movement and its impact on contemporary society. It examines how book towns have emerged and how their culture and unique characteristics help to explain a steadily growing phenomenon that has enabled peripheral communities around the world to reclaim their economic futures and impact on the cultural sphere as increasingly powerful sites and sources of creativity. Regenerating Regional Culture assesses why, at a time when the book industry is experiencing a profound transformation, book towns are proliferating in Europe and across the globe. It acknowledges the role of the book as a catalyst for this significant cultural activity and development. The book is shown to be a unique and pivotal item of cultural consumption, a remarkable artefact and, more than ever before, a springboard for contemporary cultural debate. This work investigates how the reanimation of these 'down-on-their-luck' towns is attracting, through a combination of nostalgia, history and cultural heritage, a growing middle class cohort who seek both intellectual stimulation and opportunities for serious leisure and wellbeing. This book will prove to be a useful resource for understanding the impacts of book towns on art, culture and society while also offering insightful research for those involved in existing or future development of book towns and other community cultural projects.